Foregone conclusions : against apocalyptic history - Bernstein, Michael André, 1947- (University of California Press, 1994)
Criticizes "foreshadowing" in literary works on the Shoah which view it as inevitable, as a foreordained culmination of the entire brutal history of European antisemitism. States that the Shoah was not an unavoidable tragedy, in the literary sense, because the genocide was part of an ongoing political process, and the fate of individuals sometimes depended on their own resourcefulness or on "accidental" occurrences. The Jewish victims were deluded by wrong predictions and incorrect interpretations of events, but each victim perceived his situation differently, depending on his past history, religious belief, ideology, etc. Criticizes, therefore, "backshadowing" or judging victims as though they should have known what was to come. Favors "sideshadowing"--Writing with an awareness that events do not occur because of any logical or historical necessity. Discusses mainly fictional but also non-fictional writing on the Shoah. (From the Bibliography of the Vidal Sassoon International Center for the Study of Antisemitism).
"A Centennial book."
Keywords: Apelfeld, Aharon. -- Badenhaim, ʻir nofesh; Appelfeld, Aron / Badenhaim, ʻir nofesh; Appelfeld, Aron. -- Badenhaim, ʻir nofesh; Badenhaim, ʻir nofesh (Apelfeld, Aharon); Appelfeld, Aharon, -- 1932-2018.; Holocaust, Jewish (1939-1945), in literature.; Victims in literature.; Holocaust, Jewish (1939-1945) -- Influence.; Jews -- History -- Philosophy.; Judaism and literature.; Holocauste, 1939-1945 -- Influence; Holocauste, 1939-1945, dans la littérature; Juifs -- Histoire -- Philosophie; Victimes dans la littérature; 17.93 themes and motives in literature; Languages & Literatures; Literature -- General; Holocauste, 1939-1945, dans la littérature.; Victimes dans la littérature.; Holocauste, 1939-1945 -- Influence.; Juifs -- Histoire -- Philosophie.; Judaïsme et littérature.; 17.93 themes and motives in literature.; PHILOSOPHY / Political; Holocaust, Jewish (1939-1945) in literature; Influence (Literary, artistic, etc.); Jewish philosophy; Judaism and literature; Victims in literature; Literatur; Judenvernichtung; Literaire thema's.; Joden.; Holocaust.; génocide -- Juif -- littérature -- philosophie de l'histoire.; History